A New Variant of PKLR Gene Associated With Mild Hemolysis may be Responsible for the Misdiagnosis in Pyruvate Kinase Deficiency. Issue 1 (January 2019) - Aydin Köker, Sultan; Oymak, Yeşim; Bianchi, Paola; Gözmen, Salih; Karapinar, Tuba H.; Fermo, Elisa; Vergin, Raziye C.
Abstract : Pyruvate kinase deficiency (PKD) is the most common glycolytic defect leading to hemolytic anemia. PKD is caused by the mutations in the PKLR gene; however, the detection of a decreased PK activity should be first measured for rapid diagnosis. We report here the case of a 1-year-old girl with mild hemolysis and PKD. At the time of the study, the patient showed a hemoglobin level of 9.5 g/dL, mean corpuscular volume of 93 fL, reticulocyte of 6.7%, and lactate dehydrogenase of 218 IU/L. Peripheral blood smear showed polychromasia, anisocytosis, tear drop cells, fragmented eyrtrocytes, and target cells. When a biochemical analysis was performed in our patient and her parents who had consanguinity, a decreased PK activity was detected in the patient and her father. After the molecular study of PKLR gene, a new homozygote variant, c.1708G>T (pVal570Leu), was found in our patient and her father. Her father had a misdiagnosis of Gilbert syndrome because he had unconjugated hyperbilirubinemia and not anemia. Her mother was also a carrier of the mutation in heterozygous state. Patients presenting with hemolytic anemia, either severe or mild hemolytic anemia, should be screened for PKD in the first year of life. Patients with mild hemolytic findings can be followed-up with misdiagnoses.